Tumor‐associated macrophages‐educated reparative macrophages promote diabetic wound healing - Ruoyu Mu; Zhe Zhang; Congwei Han; Yiming Niu; Zhen Xing; Zhencheng Liao; Jinzhi Xu; Ningyi Shao; Guokai Chen; Junfeng Zhang; Lei Dong; Chunming Wang (EMBO Molecular Medicine)
Abstract Nonhealing diabetic wounds, with persistent inflammation and damaged vasculature, have failed conventional treatments and require comprehensive interference. Here, inspired by tumor‐associated macrophages (TAMs) that produce abundant immunosuppressive and proliferative factors in tumor development, we generate macrophages to recapitulate TAMs' reparative functions, by culturing normal macrophages with TAMs' conditional medium (TAMs‐CM). These TAMs‐educated macrophages (TAMEMs) outperform major macrophage phenotypes (M0, M1, or M2) in suppressing inflammation, stimulating angiogenesis, and activating fibroblasts in vitro. When delivered to skin wounds in diabetic mice, TAMEMs efficiently promote healing. Based on TAMs‐CM's composition, we further reconstitute a nine‐factor cocktail to train human primary monocytes into TAMEMsC‐h, which fully resemble TAMEMs' functions without using tumor components, thereby having increased safety and enabling the preparation of autologous cells. Our study demonstrates that recapitulating TAMs' unique reparative activities in nontumor cells can lead to an effective cell therapeutic approach with high translational potential for regenerative medicine.